DIGITAL ARCHITECTURAL DESIGN METHODS: REDEFINING DESIGN THINKING IN THE COMPUTATIONAL ERA - Muntjor M.A; Vashosti M (JoDA Journal of Digital Architecture, 2026)
The increasing integration of computational technologies has fundamentally transformed architectural design processes, challenging the adequacy of conventional design thinking frameworks. This study aims to redefine design thinking in digital architectural design by positioning computation as a cognitive agent within the design process. A qualitative–experimental methodology is employed, combining parametric modeling, generative design, and performance-based simulation to examine how algorithmic workflows influence design exploration and decision-making. The research applies a case-based experimental framework to evaluate early-stage architectural design alternatives based on thermal and daylight performance criteria. The findings indicate that computational integration restructures design thinking into a non-linear, iterative system characterized by continuous feedback between human intuition and data-driven evaluation. This approach enhances decision-making efficiency, improves environmental performance, and expands the design solution space without diminishing architectural authorship. The study concludes that design thinking in the computational era requires an adaptive, data-informed framework that bridges conceptual exploration and performative assessment, offering both theoretical and practical contributions to contemporary architectural practice